Navigating tradition and treatment: cultural identity, social expectations, and type 1 diabetes self-management among young Saudi adults–a qualitative narrative inquiry - Abdulaziz M. Alodhailah; Mohammed Almutairi; Ahmed Alsadoun; Raeed Alanazi; Zainab Alfar; Thurayya Eid; Waleed M. Alshehri (Frontiers in Public Health, 2026)
Background Type 1 diabetes (T1D) requires lifelong, intensive self-management that intersects with cultural practice in collectivistic societies, where communal food traditions, religious observance, and family expectations shape daily routines. Despite an estimated incidence of 18–20 per 100,000 annually in Saudi Arabia, qualitative evidence examining how young adults navigate disease management alongside cultural identity remains limited. Objective This study explored how young Saudi adults with T1D experience and negotiate the interplay between cultural traditions, social expectations, and diabetes self-management in everyday life. Methods A qualitative narrative inquiry design was employed. Fourteen Saudi adults (aged 18–30 years) with a confirmed T1D diagnosis of at least 1 year were recruited through purposive and snowball sampling. Semi-structured interviews were conducted in Arabic, translated using a forward-backward protocol, and analyzed through reflexive thematic analysis. Reporting followed the Consolidated Criteria for Reporting Qualitative Research (COREQ). Results Five interconnected themes emerged: (1) the invisible struggle of managing a hidden condition; (2) cultural food negotiations within social contexts; (3) Ramadan as a spiritual and medical challenge; (4) social camouflage and disclosure dilemmas; and (5) resilience through cultural innovation. Three narrative identity patterns, namely Journey, Warrior, and Bridge-Builder, further characterized how participants made meaning of their experiences. Deviant cases revealed family conflict, unsuccessful fasting attempts, and persistent concealment that participants described as harmful to their self-management. Conclusion Young Saudi adults with T1D exercise genuine cultural agency in integrating traditional practices with biomedical management. These findings support culturally responsive care models that treat cultural knowledge as a clinical resource rather than a barrier, and point to the need for family-inclusive diabetes education and collaborative pre-Ramadan planning. Future research should use longitudinal designs, incorporate clinical outcome measures, and extend inquiry to rural Saudi and Gulf Cooperation Council populations.